Zeolit Sebagai Adsorben Pengolahan Air Gambut - Arhamny Arhamny; Lita Darmayanti; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Palm Oil Fly Ash (POFA) is one of the solid wastes produced in the burning of shells and palm fibers in the boiler furnace at a palm oil mill. POFA has a high silica content so that it can be used as a basis for making zeolites. Zeolite can be used as an adsorbent in water treatment, one of which is as an adsorbent in peat water treatment. The adsorption process uses absorbents to absorb metals and other impurities. Keywords: POFA, Zeolite, Adsorbent, Peat water